Psychometric Properties of a German Online Version of the Gudjonsson Suggestibility Scale 1 - Hein, Fee-Elisabeth; Scheuble, Vera; Beauducel, André; Leue, Anja (Frontiers in Psychology, 2021)
Suggestibility is a trait dimension that has been differentiated into Yield and Shift dimensions. Yield refers to the susceptibility to suggestive item content in a first question series (Yield 1) and a second question series following negative feedback (Yield 2). Shift describes the tendency to change answers over the two series of questions depending on social pressure. This study aimed at investigating the psychometric properties and the factor structure of a German online version of the Gudjonsson Suggestibility Scale 1 (GSS 1) and measurement invariance of suggestibility scores for gender and research institution. A total of N=560 (n=287 female; age: M=24.20, SD=4.60years) students participated in the study. We present Stanine norms for the application of the online GSS 1. Results supported the theoretical basis of the GSS by revealing the two expected suggestibility factors: Yield and Shift. As expected, a leading factor and a non-leading factor were identified for Yield 1 and Yield 2 and a single factor for Shift. We report psychometric properties (e.g., item difficulty, part-whole corrected item-total correlations, reliability coefficients). We compare the factorial structure of the German online GSS 1 with former versions of the GSS 1. Our data suggest widely measurement invariance for gender and research institution on Yield 1 and Yield 2.